PENGARUH TENAGA KERJA, BAHAN BAKU DAN TEKNOLOGI TERHADAP PRODUKSI INDUSTRI FURNITUR ROTAN DI KOTA DENPASAR - Luh Gede Meydianawathi, I Made Indrayana Putra (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The purpose of this study is to analyze the effect of labor, raw materials and technology simultaneously and partially and to find out the most dominant variables affecting the production of the rattan furniture industry in Denpasar City. This study uses primary data with a sample size of 32 respondents, and analyzed using multiple regression analysis techniques. The results of the data analysis show that labor, raw materials and technology simultaneously influence the production of the rattan furniture industry in Denpasar City. Partially, labor and raw materials have a positive effect on the production of rattan furniture in Denpasar City. Respondents who use modern technology produce higher production compared to respondents who do not use modern technology in their production processes. Rattan furniture entrepreneurs in the city of Denpasar are expected to pay more attention to labor as a human resource who is very instrumental in completing production and employers are compensating for the use of modern technology in the production process so that it can help the workforce, improve time efficiency and accelerate the performance of the workforce in conducting the production process